ANALISIS IMPLEMENTASI KEBIJAKAN PELAYANAN KELUARGA BERENCANA BERGERAK DI PROVINSI DKI JAKARTA TAHUN 2019 - Windi Sari Astuti; Bambang Shergi Laksmono (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
Based on the 2017 IDHS, the unmet need for DKI Jakarta Province was 15.7%, this figure is still above the national average of 10.6%. This shows that there are still problems in fulfilling contraceptive needs for PUS in DKI Jakarta Province. One of the national family planning (FP) policies in increasing access to FP services is through mobile FP services with a focus on serving Long Acting Methods (LAM). The implementation of the movement of LAM services is a strategic effort by the DKI Jakarta Provincial Office of Empowerment, Child Protection and Population Control in increasing fertile age couples participation in LAM so that it is expected to reduce the Total Fertility Rate (TFR). The research used a qualitative descriptive method which aims to describe how the implementation of mobile FP service policies in DKI Jakarta Province which is regulated in the Regulation of the Head of BKKBN Number 10 of 2018 concerning the Implementation of Mobile FP Services seen from the Communication, Resources, Bureaucratic Structure and the Attitudes of FP Program Managers and Implementers and to identify obstacles in implementing the policy. In-depth interviews were conducted with 11 administrators and implementers of FP policies who were selected based on purposive sampling technique. The results showed that communication from the management level was carried out routinely through coordination meetings. There is support for regulatory guidelines for program implementers. There is a commitment from the managers and implementer in an effort to achieve the target of increasing participation in LAM. The obstacle is the lack of number of field FP personnel which can affect the implementation of tasks to be less than than optimal.